EQUITABLE DISTRIBUTION OF FCPS PART 2 (PSYCHIATRY) TRAINEES AMONG ACCREDITED TRAINING INSTITUTES IN SINDH - Awan, Inayatullah (Journal of Pakistan Psychiatric Society, 2024)
There is a dire need to take effective steps to ensure equitable distribution of FCPS Part 2 (Psychiatry) trainees among accredited institutes in Sindh.